Open-Source Code-Based Tidal Modeling of Tropical and Temperate Waters - Srikanth, Narasimalu; Kannappan, Lakshmanan (Frontiers in Energy Research, 2021)
Tidal energy is the most reliable and predictable form of renewable energy capable of ensuring energy security in coastal regions of the world. Many developing countries are prone to energy self-sufficiency due to a lack of tidal data, expensive commercial tidal modeling tools, and program codes. In the present study, an open-source finite element code along with available open-source data was used to predict the tidal resource potential of sites in both temperate and coastal waters. This paper also investigates the suitability of open-source code towards accurate tidal resource prediction and provides a comparative study on tidal resource prediction of sites in both temperate and coastal waters. Based on knowledge gained from tidal experts all around the globe, the straits of the Alderney race were selected as a temperate water site because of their high tidal flow conditions and high tidal energy resource potential. Singapore was selected as a tropical water site because of its low tidal flow conditions and lack of open-source tidal resource data in the tropical belt. From the results, temperate waters such as Alderney Race experience high tidal velocity in the range of 3.5–4.5 m/s with an average power density of about 15 kW/m2 in comparison with tropical waters such as Singapore that experiences tidal velocity in the range of 1–1.5 m/s with an average power density of about 1.5 kW/m2. The thrusting force behind the coastal dynamics is mainly due to tides, their interactions, and changes in seabed topography. The seabed roughness profile creates a drag force on the flow on the velocity field. Lack of understanding of the effects of seabed friction on tidal modeling might reduce the accuracy of the model prediction. Thus, the present study also focuses on the effects of seabed roughness on tidal prediction of Alderney race straits using the open-source finite element-based 2-dimensional depth average ocean model. It can be found that an increase in seabed friction reduces the flow velocity and thus the average power density of the location due to its major energy dissipating phenomenon for the energetic ocean flow.